Blind frequency-domain channel estimation for STBC-SC-FDE systems via redundant precoding - Yong-chuan WANG; Zi-li CHEN (Tongxin xuebao)
A blind subspace frequency-domain channel estimation algorithm based on redundant precoding was proposed for single-carrier system with frequency-domain equalization and space-time block codes (STBC-SC-FDE) over frequency-selective fading channels.Blind channel identifiability was guaranteed up to one scalar ambiguity,and the residual scalar ambiguity could be resolved.The proposed algorithm can estimate the channel impulse response of STBC-SC-FDE systems with redundant precoder only relying on the second-order statistics of the received frequency-domain signal.Simulation results confirm the proposed algorithm is stable and reliable,and has high estimation and equalization performance.